Porphyromonas gingivalis in the tongue biofilm is associated with clinical outcome in rheumatoid arthritis patients. (19th September 2018) - Ceccarelli, F; Orrù, G; Pilloni, A; Bartosiewicz, I; Perricone, C; Martino, E; Lucchetti, R; Fais, S; Vomero, M; Olivieri, M; di Franco, M; Priori, R; et al.
Summary: Several studies have suggested a link between human microbiome and rheumatoid arthritis (RA) development. Porphyromonas gingivalis seems involved in RA initiation and progression, as supported by the high occurrence of periodontitis. In this case–control study, we analysed tongue P. gingivalis presence and quantification in a large healthy and RA cohort. We enrolled 143 RA patients [male/female (M/F) 32/111, mean ± standard deviation (s.d.), age 57·5 ± 19·8 years, mean ± s.d. disease duration 155·9 ± 114·7 months); 36 periodontitis patients (M/F 11/25, mean ± s.d., age 56 ± 9·9 years, mean ± s.d. disease duration 25·5 ± 20·9 months); and 57 patients (M/F 12/45, mean ± s.d., age 61·4 ± 10·9 years, mean ± s.d. disease duration 62·3 ± 66·9 months) with knee osteoarthritis or fibromyalgia. All subjects underwent a standard cytological swab to identify the rate of P. gingivalis/ total bacteria by using quantitative real-time polymerase chain reaction. The prevalence of P. gingivalis resulted similarly in RA and periodontitis patients (48·9 versus 52·7%, P = not significant). Moreover, the prevalence of this pathogen was significantly higher in RA and periodontitis patients in comparison with control subjects ( P = 0·01 and P = 0·003, respectively). We found a significant correlation between P. gingivalis rate in total bacteria genomes and disease activity score in 28 joints (DAS28) (erythrocyte sedimentation rate) ( r = 0·4, P = 0·01). RA patients in remission showed a significantly lower prevalence of P. gingivalis in comparison with non-remission ( P = 0·02). We demonstrated a significant association between the percentage of P. gingivalis on the total tongue biofilm and RA disease activity (DAS28), suggesting that the oral cavity microbiological status could play a role in the pathogenic mechanisms of inflammation, leading to more active disease. Graphical Abstract: